Corpus-based insights into academic writing development: evidence from Indonesian EFL learners - Faiqotur Rizkiyah (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The increasing demand for English-medium academic communication in Indonesian higher education necessitates empirical understanding of how EFL learners develop academic writing competence over time. Objective: This study aims to examine longitudinal patterns of lexical development, grammatical sophistication, and metadiscourse use among Indonesian EFL undergraduates using a corpus-based analytical framework. Method: Employing a learner corpus of argumentative essays and draft–revision pairs across four academic years, this research integrates frequency and concordance analysis, lexical complexity indices, syntactic complexity measures, and metadiscourse profiling benchmarked against established academic corpora. Results: Results show a steady reduction in high-frequency general vocabulary alongside increased academic lemma use and bundle density. Lexical diversity, subordination, and nominalization rise progressively, while overall grammatical error rates decline despite a persistent complexity–accuracy trade-off. Metadiscourse analysis reveals growth in hedging, evidentiality, and authorial stance, although interactional resources remain underrepresented compared to native benchmarks. Implication: These findings indicate that EFL academic writing development is a multidimensional process requiring pedagogical support that balances lexical growth, syntactic complexity, and interpersonal stance to achieve more effective and context-appropriate academic communication. Novelty: The novelty of this study lies in its multidimensional, longitudinal corpus design that integrates lexical, syntactic, and interpersonal dimensions within a unified developmental framework, offering a replicable model for corpus-informed EAP research.